Vietnam, Thailand, and Indonesian Government Policies regarding Rice Cultivation in the Face of Climate Change - Muadz, Muhammad Darda; Muhyidin, Ali (Universitas Negeri Semarang, 2024)
The discussion about climate change adaptation usually focuses on technology or policies. It also predominantly addresses the transportation and industrial sectors. When discussing the agricultural sector, the emphasis is often on livestock farming, which indeed generates significant greenhouse gas emissions. Apart from livestock, another significant emitter in agricultural activities is rice cultivation. In the case of Vietnam, rice cultivation produces a greater amount of greenhouse gases compared to the transportation sector. However, rice cultivation is highly vulnerable to climate change. While rice cultivation is prevalent in developing countries such as Vietnam, Thailand, and Indonesia, these countries may not necessarily have sufficient resources to cope with climate change. Therefore, this study will compare how these three countries respond to the issue of climate change based on case studies of policies related to rice cultivation. The research employs the theory of ecological modernization, which seeks solutions to climate change issues through environmentally friendly technological innovations and government policies. Policies that encourage public and private sector participation in climate change prevention are also considered. The study finds that each country has a different orientation, leading to the implementation of diverse policies and technologies according to the context and history of each nation. The mentioned history refers to the history of rice cultivation in a specific country. Meanwhile, the context of each country includes factors such as the challenges faced by a country, the orientation of farmers in rice cultivation, and the role of a country in the international market.